2006
DOI: 10.1074/jbc.m600040200
|View full text |Cite
|
Sign up to set email alerts
|

DdPDE4, a Novel cAMP-specific Phosphodiesterase at the Surface of Dictyostelium Cells

Abstract: Dictyostelium discoideum cells possess multiple cyclic nucleotide phosphodiesterases that belong either to class I enzymes that are present in all eukaryotes or to the rare ␤-lactamase class II. We describe here the identification and characterization of DdPDE4, the third class I enzyme of Dictyostelium. The deduced amino acid sequence predicts that DdPDE4 has a leader sequence, two transmembrane segments, and an extracellular catalytic domain that exhibits a high degree of homology with human cAMP-specific PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 52 publications
2
28
0
Order By: Relevance
“…Recent experimental results have also shown that a PDE isoform is expressed on the outer surface of the Dictyostelium cell membrane. 58 Fig. 6A reveals the emergence followed by the disappearance of ACA oscillations predicted by our model in response to a gradual increase and decrease in the extracellular PDE concentration (Fig.…”
Section: A New Model For Camp Oscillations In Dictyostelium Exhibits mentioning
confidence: 75%
“…Recent experimental results have also shown that a PDE isoform is expressed on the outer surface of the Dictyostelium cell membrane. 58 Fig. 6A reveals the emergence followed by the disappearance of ACA oscillations predicted by our model in response to a gradual increase and decrease in the extracellular PDE concentration (Fig.…”
Section: A New Model For Camp Oscillations In Dictyostelium Exhibits mentioning
confidence: 75%
“…Cells were then stimulated with an oversaturating dose of 2Ј-deoxy-cAMP to eliminate the responses to the intracellular as well as newly synthesized cAMP (11). In the presence of DTT, which inhibits most PDE activity (2,33), cells accumulate newly produced cAMP upon 2Ј-deoxy-cAMP stimulation (11). We observed that wild-type cells accumulated cAMP (Fig.…”
Section: Downloaded Frommentioning
confidence: 81%
“…Secreted PDE activities in CM and intracellular PDE activities in cell lysates were determined by measuring the hydrolysis of [ 3 H]cAMP, as previously described (2). PIP 3 levels were measured as described previously (35).…”
Section: Methodsmentioning
confidence: 99%
“…For example, the slime mold Dictyostelium discoideum secretes cAMP as a signaling molecule. Importantly, a recent study identified and characterized an ecto-PDE in D. discoideum that has a catalytic domain with a high degree of homology with that of mammalian PDE8 (Bader et al, 2006). A mammalian enzyme similar to the D. discoideum ecto-PDE remains to be identified.…”
Section: Discussionmentioning
confidence: 99%